DEVELOPMENT OF LOCAL COMMUNITIES ON THE BASIS OF EXPERIMENTAL BOTTOM STATIONS IN DIFFERENT ZONES OF THE NORTH-CASPIAN SHELF - Vladimir B. Ushivtsev; Sergey V. Vostokov; Nikita B. Vodovsky; Maya L. Galaktionova; Gulnara А. Akhmedova (Юг России: экология, развитие)
Aim. On the basis of four experimental bottom stations installed at various depths of the North Caspian shelf, the local communities of marine organisms were formed, on various constructions and in close proximity to them were investigated. The aim of the work is to study the features of community development on the basis of bottom biological stations, to measure their quantitative characteristics, to assess the informative character of the structural and functional characteristics of local communities for analyzing the state of the marine environment. Methods. Experimental bottom stations were installed in various regions of the North Caspian shelf using diving equipment to study their impact on the environment. Control over the development of associated fauna was carried out with the help of traps and the method of direct accounting for the materials of photo-video surveys. Sampling of fouling was carried out by the method of registration sites. Based on the number of species of flora and fauna of local communities, a ballroom information system has been suggested, that can be used for monitoring. Results. Research materials indicate a significant difference in the species composition, biomass and the structure of communities of local cenoses formed at the bottom stations with the same design and ecological capacity at various depths of the North Caspian shelf. In the shallow shelf zone at depths of 6-8 m in the local community of the bottom station, the vegetation component is dominant. At great depths, the total biomass increases in local cenoses and animal communities, including filter-feeders, make significant contribution to the self-purification of the marine environment. Conclusions. The results indicate the possibility of using complex observations of the structure and functional characteristics of local communities formed on the base of bottom stations, as well as the development of species of indicators and objects of accumulation of toxicants for assessing the state of the marine environment. The development of this approach involves the experiments with different station costructioons and materials and use of biotechnology implantation of test organisms on the design of bottom stations.